1992
DOI: 10.1136/ard.51.1.87
|View full text |Cite
|
Sign up to set email alerts
|

General joint hypermobility and temporomandibular joint derangement in adolescents.

Abstract: Joint mobility was assessed in each member of an epidemiological sample of 96 girls and 97 boys, 17 years old, and graded by means of the hypermobility score of Beighton et al. Twenty two per cent of the girls and 3% of the boys could perform five or more of the nine manoeuvres. The prevalence of symptoms and signs of internal derangement in the temporomandibular joint was higher in adolescents with hypermobility of joints (score 35/9). In subjects with a high mobility score oral parafunctions (overuse) correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 22 publications
2
31
1
2
Order By: Relevance
“…The GJH was assessed by the Carter and Wilkinson's criteria, modified by Beighton 29 , which have been used in numerous studies 4,6,[11][12][13][14][15][16] about hypermobility. Beighton's score assesses 9 joints by means of 5 tests: passive thumb opposition to the anterior portion of the forearm, until they touch; passive dorsiflexion of the little finger until it comes parallel to the forearm; elbow and knee hyperextension higher than 10 degrees; trunk flexion with the knees completely extended, in such a way that the palms of the hands touch the floor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The GJH was assessed by the Carter and Wilkinson's criteria, modified by Beighton 29 , which have been used in numerous studies 4,6,[11][12][13][14][15][16] about hypermobility. Beighton's score assesses 9 joints by means of 5 tests: passive thumb opposition to the anterior portion of the forearm, until they touch; passive dorsiflexion of the little finger until it comes parallel to the forearm; elbow and knee hyperextension higher than 10 degrees; trunk flexion with the knees completely extended, in such a way that the palms of the hands touch the floor (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that although the TMJ is among hypermobile joints, it may predispose some patients to subluxation, although not necessarily with pain or dysfunction 4 . Numerous studies 4,6,14,17 investigated GJH repercussions on joint disorders, especially disc luxation. It is believed that because of ligament laxity, the joint is overloaded, resulting in degenerative changes which may manifest itself in internal derangements and joint inflammation 18 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Still, a brief review provides clear indications of a relationship between EDS, hypermobility, and TMD. Several studies have addressed TMJ hypermobility, generalized joint hypermobility, and TMD with various conclusions [4][5][6][7][8], but with clear indication of the significant occurrence of TMD in EDS patients. Studies reported between 40% in one study and up to 100% in another, of patients presenting with multiple types of headache and/or unilateral or bilateral TMJ pain [9].…”
Section: The Effect Of Ehlers-danlos Syndromes On Tmj Function and Crmentioning
confidence: 99%